(Pro)renin Receptor-Dependent Induction of Profibrotic Factors Is Mediated by COX-2/EP4/NOX-4/Smad Pathway in Collecting Duct Cells - Reyes-Martinez, Cristian; Nguyen, Quynh My; Kassan, Modar; Gonzalez, Alexis A. (Frontiers in Pharmacology, 2019)
The binding of prorenin to the (pro)renin receptor (PRR) triggers the activation of MAPK/ERK1/2 pathway, induction of cyclooxygenase-2 (COX-2), NOX-4-dependent production of reactive oxygen species (ROS) and the induction of transforming growth factor- β (TGF-β) and pro-fibrotic factors connecting tissue growth factor (CTGF) and plasminogen activator inhibitor (PAI-I) in collecting duct (CD) cells. However, the role of COX-2 and the intracellular pathways involved are not clear. We hypothesized that the PRR activation increases profibrotic factors through COX-2-mediated PGE2 activation of E prostanoid receptor 4 (EP4), upregulation of NOX-4 / ROS production and activation of Smad pathway in mouse CD cells. Recombinant prorenin increased ROS production and protein levels of CTGF, PAI-I and TGF-β in M-1 CD cell line. Inhibition of MAPK, NOX-4 and COX-2 prevented this effect. Inhibition of MEK, COX-2 and EP4 also prevented the upregulation of NOX-4. Because TGF-β activates Smad pathway, we evaluate phosphorylation of Smad2 and 3. COX-2 inhibition or EP4 antagonism significantly prevented phosphorylation of Smad 2/3. Mice that were infused with recombinant prorenin showed an induction in the expression of CTGF, PAI-I, TGF- β, fibronectin and collagen I in isolated collecting ducts as well the expression of as alpha smooth muscle actin (a-SMA) in renal tissues. COX-2 inhibition prevented this induction. These results indicate that the induction of TGF-β, CTGF, PAI-I and ROS occurs through PRR-dependent activation of MAPK and NOX-4 however; this mechanism depends on COX-2-derived PGE2 production, the activation of EP4 and Smad pathway.